Prognostic factors in chronic lymphocytic leukaemia: the importance of age, sex and response to treatment in survival. A report from the MRC CLL 1 trial. MRC Working Party on Leukaemia in Adults. - Catovsky, D; Fooks, J; Richards, S (1989)
We report the analysis of prognostic factors in a cohort of 660 patients entered in the first Medical Research Council trial in chronic lymphocytic leukaemia (CLL) between 1978 and 1984. The majority (94%) of patients were aged 50 or over and the number of men (M) was almost twice that of women (F) with an M:F ratio of 1.8:1. The M:F ratio was lower, 1.5:1, in patients aged 70 or over. Stage A CLL was the most common, and stage C the least common, among women of all ages, in contrast to men for whom stage A only predominated in the older age group. As the majority of CLL patients are elderly we have examined the causes of death in great detail. 29% of deaths were unrelated to CLL, mainly other cancers (12%) and cardiovascular complications (16%). The majority of deaths in patients presenting with stages B and C were from CLL-related causes, whilst almost half of the deaths in patients presenting with stage A were not obviously related to CLL. Univariate analysis disclosed that the A, B, C staging system was the most important factor considered; stratified and multivariate analysis showed that age and response to treatment were the main prognostic factors after stage. Women always fared better than men and this was independent of stage and age. This and other features documented in the trial suggest a major biological difference between the sexes which has not been widely recognized. The significant influence of treatment response on patients' survival suggests that the search for better treatments in CLL may be rewarding. The improved median survival of stage C patients recorded in this trial, 41 months, compares favourably with previous reports and may have resulted from better treatment.